(untitled) (Malaysian Journal of Civil Engineering, 2018)
Ultrasonic Pulse Velocity (UPV) measurement is one of the most popular nondestructive techniques used in the indirect assessment of mechanical properties of concrete. This paper investigates the compressive strength-UPV relationship of palm kernel shell concrete (PKSC) to develop strength based quality assurance model for construction of vegetative lightweight concrete pavement. A total of 420 cubes (150mm) and 28 PKSC slabs were casted for nominal mixes of 1:1:1, 1:1:2, 1:11/2:3 and 1:2:4 and varying water/cement (w/c) ratios of 0.3-0.7. The PKSC elements were cured in water at laboratory temperature for 3, 7, 14, 21, 28, 56 and 91 days, and then subjected to nondestructive testing using the Pundit apparatus for determination of the respective ultrasonic wave velocity and elastic modulus at the various ages. The unconfined compressive strength of the PKSC was determined after the pulse velocity to establish a velocity-strength data set, which was employed for the development of statistical model. Results show that the UPV and the compressive strength of PKSC increased with age but decreased with increase in w/c ratio and mixes. The strength-UPV models developed for all mixes were in the form of logarithm equation, at R2 values of over 90%. The application of the developed model as rigid pavement maintenance/deterioration planning and design was demonstrated in the paper.